Behavior of Almsgiving and Food Offering for Monks’ Health - ธนสมบัตินันท์, ลลิลทิพย์ (Journal of Buddhist Studies Chulalongkorn University, 2016)
This article analyzes the beliefs and practices of Buddhists regarding almsgiving and food offering to monks, and monks’ dietary behaviors. It studies appropriate ways of giving alms and offering food, and proper diets for the promotion of monks’ health. The research fi nds that monks’ healthiness could be promoted through the collaboration between monks, Buddhists, and others who support Buddhist activities. This can be explained by the concept of “Merit” that creates positive interactions between monks and Buddhists. The practices of almsgiving and food offering aim to support monks in maintaining their monkhood and performing their duties in propagating Buddhism. Thus, the issue of promoting monks’ health as a result of almsgiving and food offering will be examined through “Practical Buddhism,” and the dietary behaviors of monks through the concepts of health and nutrition.